LARANGAN MENCAMPURADUKKAN AGAMA DENGAN POLITIK DALAM PEMILU TELAAH QS. AL-BAQARAH AYAT 41 - Naila Khafwa Nur (Program Studi Ilmu Al-Qur’an dan Tafsir, Fakultas Ushuluddin, Universitas Annuqayah (UA), 2025)
This study examines the prohibition of mixing religion with politics in the context of elections, based on QS. Al-Baqarah verse 41. The research is motivated by the phenomenon of using religion as a political tool, which can undermine the values of faith and justice in the democratic process. The aim of this study is to analyze the meaning of the verse and its implications for the separation between religion and politics during elections. This research employs a literature review method using both classical and contemporary Qur’anic interpretations. The findings indicate that the verse warns believers not to trade religious principles for worldly gains such as political power, highlighting the importance of preserving the purity of religion and political integrity. In conclusion, applying the principle of separating religion from politics in elections can help uphold justice and moral integrity in Indonesia’s democratic system.